Mobile Assisted Language Learning: A Close Look of Students’ Practices - Karani, Sekar Cahya (UM Purwokerto Press, 2025)
This research investigates the learning behaviors and views of eleventh-grade students using Mobile Assisted Language Learning (MALL) in a Senior High School in Cilacap, Indonesia. The findings reveal that mobile cellular technology has positively impacted English language learning, offering flexibility, access to unlimited knowledge, and interactive experiences. Students engage in various applications like Duolingo, Cake, EF Blog, and others. However, challenges include dependence on mobile devices, lack of in-depth understanding, and potential impacts on eye health. Despite obstacles such as internet instability and quotas, students exhibit a willingness to improve their English proficiency through mobile learning. The study suggests significant pedagogical implications, emphasizing the need for curriculum design that incorporates captivating and concise language activities aligned with learners' expectations. Additionally, it advocates for students to maintain consistency in their studies while using mobile technology prudently for English language enhancement.